Analisis Gen 12SrRNA Dari DNA Mitochondria Kelelawar Pemakan Buah Chironax Melanocephalus (Chiroptera: Pteropodidae) Di Taman Nasional Gunung Halimun - Zein, M. Syamsul Arifin; Maharadatunkamsi, Maharadatunkamsi (Universitas Atma Jaya Yogyakarta, 2003)
A study on genetic variation of the high mountain fruit bat (Chironax melanocephalus) was conducted in Gunung Halimun National Park. DNA total from liver tissues were extracted and fragment of the 12SrRNA gene region of mitochondrial DNA were amplified by Polymerase Chain Reaction (PCR). Nucleotide sequence of the PCR products were determined by automated sequencer. Seven haplotype were found among 20 individuals from 6 localities, namely: South Halimun Mountain, Kendeng Mountain, Botol Mountain, Pasir Cangkuang Mountain, Kencana Mountain, and Buligir Putih Mountain. Haplotype diversity and nucleotide diversity were 0.76 and 0.0222. DNA distances values ranged from 0.0028 to 0.0202.